Pulmonary Hypertension: State-of-the-Art in Pathophysiology and Management - Vinall, Phil (MD Conference Express, 2009)
This article discusses the progress that is being made toward a better understanding of the pathophysiology of pulmonary arterial hypertension (PAH), PAH diagnosis, links between genetics and PAH, as well as combination therapies for this disease, among other things.